South China Sea records Late Miocene reorganization of western Pacific deep circulation - Shan Liu; Hui Chen; Ming Su; Kunwen Luo; Jiawang Wu; Ya Gao; Zheng Meng; Sara Rodrigues; Debora Duarte; Zhi Lin Ng; Zhen Sun; Haiteng Zhuo; et al. (Nature Communications)
Abstract Oceanic gateways play a crucial role in controlling global ocean circulation. However, gateway effects on low-latitude deep-water circulation are poorly understood. The South China Sea, located in the western Pacific, was influenced by changes in the equatorial and low-latitude gateways, which recorded significant oceanographic variations since the Oligocene. Here, we identify contourite features in the deep South China Sea from seismic data and drill cores from Ocean Drilling Program Leg 184 and International Ocean Discovery Program Expeditions 349 and 367/368, as evidence for the influence of Circumpolar Deep Water originating from the eastern Indian Ocean until ca. 10 Ma. Final closure of the deep Indonesian Gateway at ca. 10 Ma caused disruption of the deep-water connection between the Pacific and Indian Oceans and a reorganization of global deep-water circulation. These changes in gateway tectonics may significantly contribute to the Middle to Late Miocene global climate and oceanic conditions.